Expression of p63 in Cervical Intraepithelial Neoplasia (CIN) and Cervical Cancer - Das, Reba; Mouri, Mahfuza Jebun; Mir, Ratim; Begum, Shahnaj; Mudi, Nondita; Kabir, Enamul (Sir Salimullah Medical College Journal, 2022)
Background: Cervical cancer is a major public health problem worldwide. Persistent infection with High-Risk Human Papilloma Virus (HPV) has been the main cause of squamous intraepithelial neoplasia which in turn leads to invasive squamous cell carcinoma. p63 is necessary for the activation of HPV, epithelial proliferation and differentiation. It also regulates the expression of certain cell cycle regulators. It has been reported that, from CIN I to CIN III, p63 expression increases progressively from basal layer to surface. In squamous cell carcinoma, it is expressed throughout the entire thickness of the tumor. Thereby it plays a significant role in diagnosing cervical premalignant and malignant lesions. Objective: To evaluate the relationship of p63 expression with different grades of CIN & invasive SCC. Method: Total 86 paraffin embedded tissue blocks of histopathologically diagnosed cases of CIN and cervical cancer were evaluated by immunohistochemical staining for p63 expression. The study was performed in Sir Salimullah Medical College, Dhaka (from March, 2018 to February, 2020). Statistical analyses were carried out by using SPSS version 22 for Windows. A descriptive analysis was performed for all data. Observations were indicated by frequencies and percentages. Statistical significance was set at “p” value <0.05. Results: Present study showed progressive increase in p63 expression from CIN I to CIN III from basal layer to surface. In invasive squamous cell carcinoma, higher expression of p63 was noted throughout the entire thickness of the tumor. No expression was seen in cervical adenocarcinoma and small cell carcinoma. In adenosquamous carcinoma only the area showing squamous differentiation revealed positive p63 expression. Statistically significant association of p63 expression was found with parity of patients and among grades of CIN . Conclusion: The results of this current study revealed that, p63 has significant association among different grades of CIN. It is also a useful marker in confirming a poorly differentiated squamous cell carcinoma & predicting the progression of a squamous neoplastic lesion from cervical intraepithelial neoplasia to invasive squamous cell carcinoma. Moreover, it is useful to differentiate invasive squamous cell carcinoma from cervical adenocarcinoma. Sir Salimullah Med Coll J 2021; 29(2): 141-146